2021
DOI: 10.1111/clr.13829
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soft tissue augmentation procedures around dental implants on marginal bone level changes—A systematic review

Abstract: Objectives This systematic review assessed the influence of soft tissue augmentation procedures on marginal bone level changes in partial or fully edentulous patients. Material and Methods We identified three relevant PICO questions related to soft tissue augmentation procedures and conducted a systematic search of four major electronic databases for clinical studies in systemically healthy patients receiving at least one dental implant and a minimum follow‐up of one year after implant placement. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
(186 reference statements)
3
24
0
Order By: Relevance
“…Recently, Stefan, et al conducted a systematic review and they reported that soft tissue augmentation is beneficial regarding width of keratinized mucosa and midfacial recession and showed no influence regarding peri implant MBL [ 21 ]. Similarly, Angelis et al found that SCTG improve peri implant soft tissue thickness and alleviate soft tissue recession and marginal bone loss when placed simultaneously with IIP protocol [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Stefan, et al conducted a systematic review and they reported that soft tissue augmentation is beneficial regarding width of keratinized mucosa and midfacial recession and showed no influence regarding peri implant MBL [ 21 ]. Similarly, Angelis et al found that SCTG improve peri implant soft tissue thickness and alleviate soft tissue recession and marginal bone loss when placed simultaneously with IIP protocol [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For type 4 implant placement, STA could better preserve the mid‐facial soft tissue thickness (Raghoebar et al, 2021). However, STA had a limited effect on the interproximal bone level (Fickl et al, 2021) and patient‐reported outcome measures (Stefanini et al, 2021). In the future, studies investigating STA for implants in aesthetic areas should (1) develop validated and reliable sets of clinical outcome measures to comprehensively evaluate the clinical, aesthetic and patient‐reported outcomes of STA; (2) focus on the improvement of grafting materials and surgical techniques, to reduce or avoid the morbidity associated with harvesting autogenous connective tissue (Thoma et al, 2021) and (3) emphasize the diagnosis and prevention of the risk factors for aesthetic failures (Thoma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For type 4 implant placement, STA could better preserve the mid-facial soft tissue thickness (Raghoebar et al, 2021). However, STA had a limited effect on the interproximal bone level (Fickl et al, 2021) and patientreported outcome measures (Stefanini et al, 2021) (Thoma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Following a dental extraction, the alveolar ridge can undergo up to 50% dimensional changes within 12 months [ 6 ]. Even with ridge preservation techniques, the alveolar ridge cannot be preserved entirely [ 7 , 8 ]. Additional hard and soft tissue augmentations around the implant can aid in maintaining stable alveolar bone and provide healthier peri-implant tissues [ 9 ].…”
Section: Introductionmentioning
confidence: 99%